2016
DOI: 10.3354/meps11814
|View full text |Cite
|
Sign up to set email alerts
|

Seawater acidification more than warming presents a challenge for two Antarctic macroalgal‑associated amphipods

Abstract: Elevated atmospheric pCO 2 concentrations are triggering seawater pH reductions and seawater temperature increases along the western Antarctic Peninsula (WAP). These factors in combination have the potential to influence organisms in an antagonistic, additive, or synergistic manner. The amphipods Gondogeneia antarctica and Paradexamine fissicauda represent prominent members of macroalgal-associated mesograzer assemblages of the WAP. Our primary objective was to investigate amphipod behavioral and physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 77 publications
1
18
0
Order By: Relevance
“…Desmarestia anceps and D. menziesii and their associated amphipods were collected by hand with mesh bags in March 2013 (see techniques in Huang et al 2007) using SCUBA at depths ranging from 5 to 30 m at 3 sites within 3.5 km of the US Palmer Station, Anvers Island, on the WAP (64°46' S, 64°03' W). The macroalgae and amphipods were processed using the methods of Schoenrock et al (2015) and Schram et al (2016b). In brief, amphipods Gondogeneia antarctica were care fully sorted for similar-sized adults and were maintained in 4 l plastic Nalgene bottles fitted with fine-mesh screening.…”
Section: Study and Sample Collection Locationmentioning
confidence: 99%
See 4 more Smart Citations
“…Desmarestia anceps and D. menziesii and their associated amphipods were collected by hand with mesh bags in March 2013 (see techniques in Huang et al 2007) using SCUBA at depths ranging from 5 to 30 m at 3 sites within 3.5 km of the US Palmer Station, Anvers Island, on the WAP (64°46' S, 64°03' W). The macroalgae and amphipods were processed using the methods of Schoenrock et al (2015) and Schram et al (2016b). In brief, amphipods Gondogeneia antarctica were care fully sorted for similar-sized adults and were maintained in 4 l plastic Nalgene bottles fitted with fine-mesh screening.…”
Section: Study and Sample Collection Locationmentioning
confidence: 99%
“…Previous studies have demonstrated that prominent representatives of macroalgae−mesograzer as semblages along the Antarctic Peninsula exhibit contrasting responses to chronic exposure to OWA (Schoenrock et al 2015, Schram et al 2016b. For example, 2 of the most conspicuous benthic canopy-forming macro algae, D. menziesii and D. anceps, ex hibited few responses when exposed to OWA, with no significant changes detected in photosynthetic para meters, overall growth, or concentrations of chlorophyll a (Schoenrock et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations